Berita Harian, 14 Oktober 2015 - Hamizar Hamid; Hamizar Hamid; Hazwan Faisal Mohamad; Luqman Arif Abdul Karim; Syed Azwan Syed Ali (Berita Harian, 2015)
Laporan akhir siasatan sah pesawat ditembak guna peluru berpandu.